Flood Mitigation Approaches: Selected Cases Across Europe, Oceania and Asia - Abdul Rahman, Nazri; Jamaludin, Mohd Safri; Wai Tan, Lai; Md Ali, Zarina; E. Pinilla, Camilo (International Journal of Sustainable Construction Engineering and Technology, 2022)
Flood is natural phenomenon that cannot be completely controlled by man. Flood is a global problem. Even urban areas which have good development planning and drainage systems are susceptible to floods. Flooding in urban area is usually associated with poor drainage system maintenance, failure to plan drainage system, area development is not planned properly, and climate change factors. Typically, engineering measures are meant to reduce severity of flood problems and they are quite costly. Goal of this paper is to assess the various mitigation approaches that have been used to mitigate floods across Europe, Oceania and Asia continents. Selected case studies involving the North Sea flood, as well as floods in the Netherlands, Scotland, New Zealand, Australia, Hong Kong, Taiwan, Singapore and Malaysia were considered. Approaches that were highlighted include construction of dam, breakwater, canal, and pumping system. It has also been found that flood solution methods by way of source control is not so popular to be fully practiced. Hence, the sustainability of good development is actually a solution to problem of flooding, especially to mitigate flash floods that often occur in an urban areas.